Calendar Anomalies : Existence and Persistence - Khanna, Vandana (Indian Journal of Research in Capital Markets, 2016)
Predicting the behavior of the stock market is considered as one of the most challenging tasks performed by securities analysts and researchers the world over. The presence of calendar anomalies in stock markets has been one of the most researched topics of research amongÂ economists, academicians, statisticians, and market experts for many decades because it provides the possibilities of making unusual profits for investors. Many surveys have been conducted not only in developed countries like the UK, but also in emerging markets like China in order to provide evidence for the presence of any stock market anomalies. Globally, evidence of seasonal anomalies in stock market returns has generated considerable interest among the general public in recent years, and a significant amount of research has been devoted towards documenting the existence and potential of an anomaly for generating superior risk-adjusted returns. Even so, for decades, investors, whether individual or institutional, have always been interested in finding an answer to the question of how securities are priced (Ziemba & Hensel, 1994). To fill this gap in research in presence of calendar anomalies, the present literature review study examined major calendar anomalies prevailing in India and abroad. The current study stressed examining their existence and persistence in the economy domestically or internationally. For this purpose, most of the studies conducted in the period from 1953 upto 2016 have been considered.